#TITLE_ALTERNATIVE# - NURFITRI (NIM:12910008); Pembimbing : Dr.rer.nat Mutiara Rachmat Putri, S.Si, M.Si., SULISKANIA
Data assimilation technique was appllied into 2-dimensional vertical (2-DV) transport model of temperature. Simulation was doing in Tropical Pacific Ocean, 2°N and 137°E – 140°W with two open boundary conditions on the west and the east. Time varying temperature data was added in two open boundary as model forcing. Model was running for 2 years from January 1st 2011 until December 31th 2012 from surface to 500 m depth. Assimilation of temperature data into transport model in Pacific Ocean was aim to improve model result, especially at thermocline layer which has large temperature’s change. The results of with and without assimilation show that the sea temperature has a range from 30,5°C at the surface and 7°C at 500 m depth. Temperature result from model was verified to observation data from TAO mooring at 3 locations, 147°E, 165°E, and 170°W. The largest error of model has occurred at 200 m depth, whereas the smallest at the surface and 500 m. Assimilation data procedure was applied at 3 locations, 156°E, 180°W, and 155°W using Cressman analysis technique. Assimilation data can reduce model’s RMSE toward depth until 55,7% and toward time until 64,5%. Furthermore, assimilation data procedure can also represent thermocline layer better than model without assimilation.